Usage of antibiotics and monitoring of drug interactions in pediatrics at a tertiary care teaching hospital - N., Rajasekar; M., Kireesh Kumar; M., Sowndarya; K., Dhanapal C.; R., Ramanathan (International Journal of Contemporary Pediatrics, 2021)
Background: Respiratory tract infections (RTI) are more common in pediatrics. Especially in developing countries like India, RTI causes more death in children. Antibiotics are used to treat RTI even in case of viral infections. Hence rational use of antibiotics is very much needed to avoid antibiotic resistance. In this study we have analysed the prescribing pattern of antibiotics and their drug interactions involved in the management of respiratory tract infections in a tertiary care teaching hospital. Methods: A prospective observational study was conducted in the department of pediatrics at a tertiary care teaching hospital for a period of 6 months (November 2019-April 2020). A total of 144 patients were included in the study and their prescription was analysed for their antibiotic prescribing pattern and interactions. Results: Infants were more prone to RTI infections. Among RTI, lower RTI were more common in children. We have analysed prescribing pattern of antibiotics in which, mono antibiotic therapy were more commonly used. Ampicillin was the frequently prescribed antibiotic. Azithromycin had the most possible interactions among the antibiotics prescribed. Conclusions: More than 336 antibiotics were used for all types of RTI, even in the case of viral infections. So rational use of antibiotics is needed. Among 144 children who were enrolled in the study, none of them were subjected to culture sensitivity test. As of which, all of them were treated empirically. Penicillin and cephalosporin are the mostly prescribed antibiotics in RTI. Cephalosporin prescribed children had less hospital stay and hardly interactions were found.